The impact of development finance institutions : rapid evidence assessment, June 2019 - Samantha Attridge; Rachael Calleja; Matthew Gouett; Alberto Lemma (The impact of development finance institutions : rapid evidence assessment, June 2019, 2019)
The UK Government is placing ever greater emphasis on supporting economic growth and mobilising private investment in developing countries in support of the Sustainable Development Goals (SDGs). The UK's development finance institution (DFI), CDC Group (formerly the Commonwealth Development Corporation), will play a role in achieving this goal. In October 2017, the UK Department for International Development (DFID) announced a capital increase for CDC of up to 3.5 billion, funded by official development assistance (ODA). Consequently, there is a need for better understanding of the development impact of DFI investment more broadly to inform effective policy decisions on the allocation and investment of ODA and other official financial flows. This rapid evidence assessment examines and synthesises the evidence base on the development impact of DFI investment. The objective is to strengthen DFIDs understanding of the critical assumptions underpinning its private sector development (PSD) theory of change to inform future PSD programming decisions.